Preventive product protection - guidelines and application examples - Gausemeier, Jürgen; Lindemann, Udo; Glatz, Rainer
Product piracy destroys jobs, deprives industry of the return on research and development investments and threatens the competitiveness of many companies. Protection against product imitations requires the development of innovative, technical protective measures and holistic protection concepts. This work shows how such protection concepts are developed and implemented. Central to this are the identification of the individual threat potential and the implementation of comprehensive product protection based on protective measures. Practical examples illustrate the application of the methods and tools and facilitate the practical transfer. A uniform presentation of over 90 protective measures completes the book.